Qualified analysis b/w ESB(s) using Analytical Hierarchy Process (AHP) method - Abdul Hanan, Abdullah (IEEE, 2011)
This research study stress upon the qualified or comparative analysis between commercial and noncommercial Enterprise Service Buses (ESB) for largescale organizations. We have used Multi Criteria Decision Analysis (MCDA) method known as Analytical Hierarchy Process (AHP) based on three criteria i.e. Information Security, Interoperability & High availability. Many comparative analysis reports and papers are available having proven results of comparing non-commercial ESB(s), however, very few reports were found having performed their analysis on commercial ESB(s). We have performed this analysis on the basis of tabular and mathematical proofs by comparing commercially known ESB i.e. Oracle ESB with two noncommercial yet very famous ESB(s) i.e. Mule & Fuse. This research analysis will motivate decision makers to choose the best rated ESB on the basis of our criteria. To achieve our objective we have presented the problem as hierarchy, established the priorities, criteria and performed mathematical computing to prove our analysis.